2000
DOI: 10.1038/sj.ijo.0801090
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index in 17-year-old Israeli males of different ethnic backgrounds; national or ethnic-specific references?

Abstract: OBJECTIVE: To evaluate whether a single national reference is appropriate for assessing prevalence of overweight in heterogeneous populations, or whether ethnic-speci®c references are needed. DESIGN: A population-based study of Israeli Jewish males who underwent routine physical and clinical examinations prior to army recruitment served as the basis for the development of two types of references for body mass index (BMI): a national reference (NR) and an ethnic-speci®c reference (ER). SUBJECTS: Consecutive coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
2
2
Order By: Relevance
“…In an ethnically heterogeneous population, it may not be appropriate to use a single national reference, and an ethnic‐specific reference may be preferable. Evidence to this effect has been provided previously in Israeli military recruits, who showed distinct BMI distribution patterns based on ethnic origin 26. However, origin‐based variability has not been demonstrated in younger Israeli children, and the results of the present study do not support its existence in children aged 7–11 y.…”
Section: Discussioncontrasting
confidence: 63%
“…In an ethnically heterogeneous population, it may not be appropriate to use a single national reference, and an ethnic‐specific reference may be preferable. Evidence to this effect has been provided previously in Israeli military recruits, who showed distinct BMI distribution patterns based on ethnic origin 26. However, origin‐based variability has not been demonstrated in younger Israeli children, and the results of the present study do not support its existence in children aged 7–11 y.…”
Section: Discussioncontrasting
confidence: 63%
“…It has been reported previously that BMI is influenced by background SES (Lusky et al, 2000). The present study found a strong association between nutritional status and SES.…”
Section: Discussionsupporting
confidence: 79%
“…In an ethnically heterogeneous population, it may not be appropriate to use a single national reference, and an ethnic-specific reference may be preferable. Evidence to this effect has been provided previously in Israeli military recruits, who showed distinct BMI distribution patterns based on ethnic origin [26]. However, origin-based variability has not been demonstrated in younger Israeli children, and the results of the present study do not support its existence in children aged 7 Á/11 y.…”
Section: Discussioncontrasting
confidence: 63%